No Sacrifice No Gain: Construction of Cleavable Bridged Macrobicyclic Olefins for Precision Polymers - Yu, Zhen; Wang, Li; Liu, Li; Wang, Meng; Yang, Hong (Synlett, 2022)
Olefin metathesis polymerization has commanded great attention as a versatile method for preparing macromolecular materials with advanced architectures and functions in academia and industry. This Account summarizes our endeavors directed towards the preparation of various functional polymers by using olefin metathesis polymerization strategies in particular acyclic diene metathesis (ADMET) polymerization and ring-opening metathesis polymerization (ROMP), during the last ten years. In addition, the merits and limitations of ADMET polymerization and ROMP techniques are also demonstrated and compared. Notably, this Account highlights our recently developed sequence-controlled ROMP strategy for production of precision polymers in a regio-/stereoselective manner, the rollercoaster journey for the evolution of a macrobicyclic olefin system containing a sacrificial silyloxide bridge is described in detail.1 Introduction2 Olefin Metathesis Step-Growth Polymerization Approaches3 Olefin Metathesis Chain-Growth Polymerization Approaches4 ROMP of Cleavable Bridged Macrobicyclic Olefins5 Conclusion
Keywords: olefin metathesis polymerization; precision polymer; sequence control; acyclic diene metathesis polymerization; macrobicyclic olefin; ring-opening metathesis polymerization